Revision of the Australian Sabellariidae (Polychaeta) and description of eight new species - Hutchings, Pat; Capa, María; Peart, Rachael (Zootaxa, 2012)
The family Sabellariidae is represented in Australian waters by eleven species belonging to five genera, including eight of themnew to Science: Idanthyrsus nesos n. sp., I. willora n. sp., Lygdamis wambiri n. sp., Phalacrostemma maloga n. sp., Sabellariakooraltha n. sp., S. lungalla n. sp., S. pyramis n. sp., and Tetreres terribilis n. sp. Three genera, Phalocrostemma, Sabellaria andTetreres, are newly recorded from Australia. Descriptions of all species are given, acompanied by detailed illustrations, includingdrawings, photographs and scanning electron micrographs, tables summarising specific diagnostic characters of all species ofeach genus, and distribution maps within Australia. A key to all genera worldwide and Australian species is given. Maximumparsimony analyses based on morphological features have been performed to assess the position of the new species and relation-ships with other Sabellariidae. For this purpose, the Australian species, the type species of each genus and some others species,representing the variability within each group, were incorporated into the analyses. Some of the species were recovered withinmonophyletic genera (Phalacrostemma and Tetreres), while others have been considered as member of previously recognised genera (Idanthyrsus, Lygdamis and Sabellaria) have not been assessed as monophyletic.